(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
Physical therapy of military servants with the consequences of a mine - explosive injury of the lower extremities. Prolonged military operations in Ukraine pose serious challenges for the medical system. The use of modern weapons causes significant severity of gunshot injuries, in particular to the limbs, which complicates the process of providing medical care with the aim of restoring anatomical integrity and functional capabilities as quickly as possible. Purpose of the study: to theoretically substantiate the features of physical therapy for military personnel in restoring upper limb functions in military personnel after gunshot wounds to the shoulder. The work used theoretical research methods: analysis, comparison, induction, deduction, systematization and generalization of scientific and methodological literature. Physical therapy for military personnel is an important component of the recovery process after injuries, in particular gunshot wounds, and contributes not only to physical but also to psychological recovery. During rehabilitation, it is important to apply an individual approach to each patient, since the nature of the injuries, the physiological state and the needs of military personnel can vary significantly. The use of therapeutic exercises requires the patient’s active participation in the process of physical therapy, forming a conscious attitude towards performing exercises and participating in adjusting their motor regimen. It is important to approach each patient individually, taking into account not only the type and degree of injury, but also other factors such as age, functional impairment, level of physical fitness and psychological state. Thus, effective rehabilitation of military personnel with gunshot injuries of the shoulder requires a deep understanding of the specifics of the injuries, individual characteristics of the victims and the use of innovative techniques to ensure full recovery of physical and emotional health.